ANALISIS SISTEM PENGADAAN BAHAN PUSTAKA DI UPT PERPUSTAKAAN POLITEKNIK NEGERI SRIWIJAYA - Prastiwi , Anggun (Jurnal Multidisipliner Kapalamada, 2024)
This article analyzes the library material procurement system at the Sriwijaya State Polytechnic Library UPT to assess the extent to which the system has met academic needs and identifies areas that require improvement. Through qualitative descriptive research using field research methods, this article explains the definition and policy for procurement of library materials, as well as commonly used methods, such as purchase, gift, exchange, entrustment, and self-publishing. Next, this article explores the library material procurement system at the Sriwijaya State Polytechnic Library UPT in detail, which includes purchases using the APBN budget, receiving gifts and donations. The procurement process through purchasing is explained in detail, starting from identifying needs, preparing a list of proposals, evaluation and approval, procurement processes, acceptance and verification, to reporting and evaluation. By analyzing the existing procurement system, this article aims to provide insights and recommendations to improve the quality and quantity of library materials at the Sriwijaya State Polytechnic Library UPT, so that it can be more effective in supporting its vision and mission as a leading information center in the higher education environment.